2018
DOI: 10.1111/jth.14200
|View full text |Cite
|
Sign up to set email alerts
|

Management of postpartum hemorrhage: how to improve maternal outcomes?

Abstract: Postpartum hemorrhage is the leading cause of maternal mortality and severe morbidity. Despite efforts to improve maternal outcomes, management of postpartum hemorrhage still faces at least four challenges, discussed in this review. First, current definitions for severe postpartum hemorrhage hamper early identification of women with a high risk of adverse outcomes. Adaptations to the definitions and the use of clinical tools such as shock index and early warning systems may facilitate this early identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 109 publications
0
22
0
1
Order By: Relevance
“…1,2 Primary PPH is traditionally defined as 500 mL blood loss or more within 24 hours after delivery, independent of the mode of delivery. [6][7][8] The most frequent obstetrical causes of PPH are uterine atony, (partially) retained placenta or perineal trauma (episiotomy and/or lacerations). [6][7][8] The most frequent obstetrical causes of PPH are uterine atony, (partially) retained placenta or perineal trauma (episiotomy and/or lacerations).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Primary PPH is traditionally defined as 500 mL blood loss or more within 24 hours after delivery, independent of the mode of delivery. [6][7][8] The most frequent obstetrical causes of PPH are uterine atony, (partially) retained placenta or perineal trauma (episiotomy and/or lacerations). [6][7][8] The most frequent obstetrical causes of PPH are uterine atony, (partially) retained placenta or perineal trauma (episiotomy and/or lacerations).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 PPH can further be classified as minor (500-1000 mL) or major (>1000 mL) PPH, 5 with major PPH being subdivided in moderate (1001-2000 mL) and severe (>2000 mL) PPH. [6][7][8] The most frequent obstetrical causes of PPH are uterine atony, (partially) retained placenta or perineal trauma (episiotomy and/or lacerations). A history of PPH, advanced maternal age, pre-eclampsia, macrosomia and multiple gestation are known risk factors for PPH.…”
Section: Introductionmentioning
confidence: 99%
“…38,156 Potential use of Precision-Based Medicine in MAC and TIC Large randomized controlled trials regarding the empiric management of bleeding trauma and obstetrical patients have been met with differing levels of acceptances as the histories of the CRASH-2 and WOMAN trials have shown. 27,[157][158][159][160][161][162][163] Because of the unintended consequence of "one-size-fits-all" randomized controlled trial philosophy touted for the advancement of evidence-based clinical science, it is more difficult to engage in smaller proof-of-concept studies that evaluate the influence of specific pathophysiological derangements and phenotypes on clinical outcomes. 164,165 The concept of precision-based medicine has been developed to allow for the integration of epidemiologic findings from randomized controlled trials with select patient-group-specific clinical findings.…”
Section: The Spectrum Of Macmentioning
confidence: 99%
“…Postpartum hemorrhage (PPH) is the leading cause of maternal death worldwide [1][2][3], and the incidence has increased in many countries despite improvements in obstetric protocols to prevent and treat severe hemorrhage [4][5][6][7]. Specific intervention points and management strategies to define and treat coagulopathy associated with PPH are not uniform [8].…”
Section: The Utilization Of Viscoelastic Testing To Guide Blood Compomentioning
confidence: 99%
“…These large well-designed RCTs suggest that the utilization of TXA within 3 hours of bleeding, either from trauma or PPH, improved mortality. Subsequent studies have suggested that knowledge gaps in the CRASH-2 Trial and problems in defining PPH have made these trials a source of considerable and interesting discussion [7,[63][64][65][66][67][68][69][70][71][72][73][74][75][76][77]. For the other prohemostatic agents, the utilization of soluble fibrinogen in Europe and cryoprecipitate in the United States is guided by VETs and Clauss fibrinogen [10].…”
Section: Platelet Functionmentioning
confidence: 99%